Unveiling Lecturers’ Strategies Dealing with Unethical Use of AI Tools During Theses Supervising Process - Alfilail, Nur; Rahmawati, Lela; Muhid, Abdul; Hastuti, Hilda; Dewi, Ni Putu Sinta (Lembaga Intelektual Muda (LIM) Maluku, 2026)
The use of artificial intelligence (AI) in higher education, particularly in academic writing, is growing rapidly and bringing both positive impacts and ethical challenges. On the one hand, AI can assist students in writing essays and scientific papers, but on the other hand, it has the potential to encourage dependence and unethical practices, especially in thesis writing. This study aims to identify the strategies implemented by lecturers in anticipating the unethical use of AI in students' academic writing. This study uses a quantitative approach involving six lecturers from Bumigora University as respondents. Data were collected through a questionnaire and analysed descriptively. The results show that lecturers implement various strategies, including providing guidance on the ethical use of AI, checking and evaluating students' writing, and providing education on academic integrity. These findings indicate that lecturers play a very important role in guiding the responsible use of AI so that this technology can support the learning process without neglecting ethical values and academic honesty.